Beginning Hibernate from novice to professional - Minter, Dave; Linwood, Jeff (Apress, 2006)
Beginning Hibernate is ideal if you're experienced in Java with databases (the traditional, or connected, approach), but are new to open source lightweight Hibernate--the most popular de facto object-relational mapping and database-oriented application development framework. This book packs in information about the release of the Hibernate 3.2.x persistence layer and provides a clear introduction to the current standard for object-relational persistence in Java. Experienced author Dave Minter and contributor Jeff Linwood provide more in-depth examples than any other books for Hibernate beginners. The authors also present material in a lively, example-based mannernot in a dry, theoretical, hard-to-read fashion. And since the book keeps its focus on Hibernate without wasting time on nonessential third-party tools, you'll be able to immediately start building transaction-based engines and applications.